Cognitive Differences between Men and Women who Fracture their Hip and Impact on Six-Month Survival - Gruber-Baldini, Ann L. (J Am Geriatr Soc, 2017)
BACKGROUND/OBJECTIVES: There is limited research in cognition and its relationship to mortality after hip fracture among men compared to women. Therefore, the goals of this study were to: (1) compare men and women who fractured their hip on cognition after hospital discharge, and (2) examine the impact of cognition on the differential risk of 6-month mortality between men and women post fracture. DESIGN: Prospective cohort study SETTING: Eight hospitals in Baltimore, Maryland. PARTICIPANTS: Frequency matched 168 male and 171 female hip fracture patients, ages 65 or older, living in the community before fracture MEASUREMENTS: Cognition assed by Modified Mini-Mental State Examination (3MS, and derived MMSE score), Hooper Visual Organization test (HVOT), and Trail-making test (Trails A & B) within 22 days of hospital admission, and 6-month mortality. RESULTS: Men had more impaired cognitive scores on 3MS, MMSE, HVOT, and Trails A (p<.05) at baseline. These statistically significant differences between men and women remained on MMSE and HVOT after controlling for pre-fracture dementia, in-hospital delirium, age, education, race, and comorbidity. Men had higher 6-month mortality rates (HR=4.4, p<.001). Cognitive measures were also significantly associated with mortality, including 3MS, HVOT, and Trails B. Among the cognitive measures, higher 3MS was most protective for mortality (HR=0.98, p<.001), both unadjusted and adjusted for other cognitive scales, comorbidity, delirium, and pre-existing dementia. The highest mortality was among men with 3MS<78, with 26.3% dying within 6 months. The effects of cognition on mortality did not differ by sex. CONCLUSION: Men display greater levels of cognitive impairment within the first 22 days of hip fracture than women, and cognitive limitations increase the risk of mortality in both men and women.